Atomic force microscopy (AFM) and its applications to bone-related research. (December 2022) - Zhou, Yuxiao; Du, Jing
Abstract: Bone consists of organic (mostly collagen) and inorganic (mostly bioapatite mineral) components that are organized into hierarchical structures from nano-to macro-scales that provide load-bearing functions. The structures and properties of bone are affected by bone remodeling activities, which are affected by mechanotransduction, a process through which mechanical signals are converted to biochemical signals in cellular signaling. Atomic Force Microscopy (AFM) technique can be used to characterize the surface morphology and mechanical properties of the specimens and can achieve atomic resolution in the resulting images. Therefore, the AFM technique has been applied in bone research and has provided new understandings of the structures and properties of hierarchical structures in bone across multiple length scales. This review begins by introducing the tip-surface interactions and the operation modes of AFM, including the recently developed sub-resonance modes, including PeakForce Tapping mode. Then the contact adhesion theories used in analyzing AFM data are reviewed, followed by a systematic review of the applications of the AFM technique to bone and bone-related tissues and cells, including surface morphology imaging, contact indentation testing, and other mechanical tests. The applications of sub-resonance tapping mode to bone and other biological molecules, cells, and tissues are also reviewed. Highlights: Development and operation modes of Atomic Force Microscope (AFM). Contact, adhesion, indentation theories and models related to AFM. Application of AFM to research on bone and related tissues and cells. Recent advances with PeakForce mapping AFM on bone research.